Evaluation of the effect of testosterone replacement therapy with a transdermal testosterone on glycemic control in men with type 2 diabetes mellitus - R. V. Rozhivanov; M. O. Chernova; V. A. Ioutsi; G. A. Mel’nichenko; M. V. Shestakova; E. R. Rozhivanova; E. N. Andreeva; N. G. Mokrysheva (Сахарный диабет)
BACKGROUND: It is important to evaluate the effect of androgen replacement therapy on glycemic control.AIMS: Assessment of the effect of transdermal testosterone therapy on glycemic control in men with hypogonadism and T2DM.MATERIALS AND METHODS: The prospective, comparative study included 300 men aged 55[49;61] years: men receiving both glucose-lowering therapy (GLT) and transdermal testosterone; and patients receiving only GLT. Observation period 1 year. A medical history, a questionnaire for symptoms of androgen deficiency, and measurement of total testosterone and glycated hemoglobin were carried out. Groups were compared using nonparametric methods.RESULTS: Patients receiving androgen replacement therapy in combination with GLT at both 6 and 12 months from the moment of inclusion in the study, they had a statistically significantly higher level of total testosterone and less severity of symptoms of androgen deficiency. When assessing the magnitude of changes in the studied parameters, it was found that patients receiving testosterone replacement therapy (TRT) were characterized by a statistically significantly more pronounced decrease in the level of glycated hemoglobin (average difference 0,3%). In 29 (20,4% (95% ДИ 13,8–27,0)) men who received only GLT, hypogonadism was eliminated. In 3 patients from the TRT group, a pathological increase in the level of total blood PSA was observed, and therefore TRT was discontinued. An increase in hemoglobin above the reference value (>172 g/l) was detected in 8% and 1,3% of men on TRT and without correction of hypogonadism, respectively, p=0,011.CONCLUSIONS: The combination of transdermal TRT and GLT has a positive effect on glycemic control, which is manifested by a decrease in glycated hemoglobin to a greater extent than when using GLT alone. Normalization of testosterone levels leads to a decrease in the symptoms of androgen deficiency, which is accompanied by an improvement in quality of life. Elimination of hypogonadism only with GLT is possible in a small number of cases.